Synthesis, Enzyme Inhibition, and Molecular Docking Studies of Hydrazones from Dichlorophenylacetic Acids. Issue 12 (16th November 2016) - Abid, Obaid‐ur‐Rahman; Ayaz, Muhammad; Rehman, Wajid; Mehdi, Kamran; Ali, Arif; Wadood, Abdul; Rahim, Fazal; Sultan, Aneesa; Ghufran, Mehreen; Mir, Sadullah; Qureshi, Muhammad Tauseef
Abstract : A series of hydrazones5a–i were synthesized by the condensation of hydrazides derived from dichlorophenylacetic acids with different aromatic aldehydes and ketones. Their structures were confirmed by spectroscopic data and elemental analysis. Hydrazones5a–i were evaluated for α‐glucosidase and urease inhibition activities. Five compounds exhibited potent α‐glucosidase inhibitory potential with IC50 values 8.5 ± 0.3, 22.2 ± 0.78, 32.9 ± 1.5, 34 ± 2.4, and 170.6 ± 7.5 μM, respectively, which are many times better than that of the standard inhibitor acarbose (IC50 = 840 ± 1.73 μM). Furthermore, molecular docking study was performed to explore the binding mode in the active sites of α‐glucosidase and urease enzymes. Abstract : Hydrazones5a–i were synthesized by the condensation of hydrazides derived from dichlorophenylacetic acids with different aromatic aldehydes/ketones and were evaluated for α‐glucosidase and urease inhibitory potential. Five compounds exhibited potent α‐glucosidase inhibitory potential much better than the standard inhibitor acarbose. Molecular docking study was performed to explore the binding mode in the active sites of α‐glucosidase and urease enzymes.